Digital Transformation in Public Services: Adoption of the National Digital Identity System - Rangga Setiadi Rachmawan; Sri Wulandari; Hendri Suwarsono (Salus Publica: Journal of Community Service, 2026)
Digital Population Identity (IKD) is a population administration application implemented as a government policy to facilitate public access to population data. The objectives of this study are to analyze the use of IKD as a means of facilitating access to digital information, to identify barriers to its use, and to examine efforts to address these barriers. The method used in this study is research subjects are heads of population administration information management divisions, serving as key informants. The study applies Vial’s theory of digital transformation, which comprises six dimensions: the combination of information technology, organizational change, the creation of new value, organizational culture, organizational structure, and organizational strategy. The results of the study indicate that the IKD application facilitates the public’s access to digital population administration services, thereby saving time, effort, and costs. Challenges in its implementation include application glitches, network limitations, low digital literacy among some members of the public, and uneven outreach efforts.